Poligami dalam Novel Wattpad Perspektif Hukum Positif - Ulya, Zakiyatul; jiphi, Jiphie Gilia Indriyani (Faculty of Shariah UIN Ponorogo, 2024)
Polygamy as a controversial issue is always interesting to discuss, including in novels. Novels themselves are undergoing transformation along with advances in technology, from non-digital to digital, one of which is Wattpad which opens up access for users, both as readers and story writers, so that they can become a dynamic place to share and enjoy various stories from various points of view. Writers can freely convey their ideologies or opinions to readers - who inevitably, whether consciously or not - have appreciated and even guided them. In Indonesia itself, polygamy has been regulated in detail in positive law. So whether the concept of polygamy presented in the Wattpad novel is relevant to the provisions on polygamy in positive law is important to study. This study is library research with documentation techniques as the data collection technique. Three novels were chosen based on the finished story, Islamic boarding school setting, and number of readers, namely: Menjadi Yang Kedua, Antara Dua Hati dan Kenapa Sesakit Ini? The previously collected data was then analyzed using descriptive techniques with a deductive mindset. The study results show that the concept of polygamy presented in two of the three novels is not fully relevant to the provisions of polygamy in positive law, especially regarding the stages of marriage registration that must be fulfilled. At the same time, the relevance of the remaining one cannot be known because there is no clear picture of the implementation of the marriage. Justice, which is a condition for allowing polygamy, ultimately cannot be realized in the domestic life of the three novels studied.